ESSENCE, MODERN DEFINITION OF INTELLECTUAL PROPERTY AND THE PROCESSES OF ITS COMMERCIALIZATION - A.Kulembaueva, (Academic Journal of Physical and Chemical Sciences, 2019)
This article discusses the classification of intellectual property institutions, and presents a range of intellectual property objects. The article presents also the nature of their use, analyzes the domestic and foreign researchers’ scientific approaches to the problems of classifying intellectual property objects that we study. This article studies the domestic and foreign legislative framework of the definition we are studying to determine objects for commercialization.